Hemoglobin albumin lymphocyte and platelet score and all-cause mortality in coronary heart disease: a retrospective cohort study of NHANES database - Zheng, Yang; Huang, Yubing; Li, Haitao (Frontiers in Cardiovascular Medicine, 2023)
Aim: Anemia, inflammatory status, and malnutrition are all important factors in the prognosis of cardiovascular disease (CVD), and the interactions of them are also noteworthy. A recent scoring system, the hemoglobin albumin lymphocyte and platelet (HALP) score, combining multi-dimensional metrics has been used in the prognoses of many diseases except coronary heart disease (CHD). Herein, this study aims to explore the association between HALP score and all-cause mortality in patients with CHD. Methods: Demographic and clinical data of adult patients with CHD were extracted from the National Health and Nutrition Examination Surveys (NHANES) database in 2003-2018 in this retrospective cohort study. Weighted univariate and multivariate COX proportional hazard models were used for covariates screening and exploration of the association between HALP score and all-cause mortality. The evaluation indexes were hazard ratios (ORs) and 95% confidence intervals (CIs). Kaplan-Meier (KM) curve and the receiver operator characteristic (ROC) curve were used to assess the predictive performance of HALP on CHD prognosis. In addition, subgroups analyses of age and congestive heart failure (CHF) were also performed. Results: Among the eligible patients, 657 died for all cause. After adjusting for the covariates including age, education level, PIR, marital status, smoking, physical activity, total energy intake, CHF, stroke, hypertension, DM, CKD, cancer or malignancy, monocyte, drug for CVD, treatment for anemia, anticoagulants drug, and adrenal cortical steroids, we found that HALP score was negatively associated with the risk of all-cause mortality [HR=0.83, 95%CI: (0.74-0.93)]. Compared with patients with high HALP score, those who had lower HALP score seemed to have a higher risk of all-cause mortality (all P<0.05). HALP score has a potential predictive value on CHD prognosis with an area under the curve (AUC) of 0.61. Furthermore, in patients who aged <65 years old, with or without CHF, lower HALP score was also associated with a higher risk of all-cause mortality (all P<0.05). Conclusions: HALP score has a potential predictive value on CHD prognosis, and however, the causal association between HALP score and mortality in patients with CHD is needed further exploration.